-19=-11+p

Simple and best practice solution for -19=-11+p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19=-11+p equation:


Simplifying
-19 = -11 + p

Solving
-19 = -11 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
-19 + -1p = -11 + p + -1p

Combine like terms: p + -1p = 0
-19 + -1p = -11 + 0
-19 + -1p = -11

Add '19' to each side of the equation.
-19 + 19 + -1p = -11 + 19

Combine like terms: -19 + 19 = 0
0 + -1p = -11 + 19
-1p = -11 + 19

Combine like terms: -11 + 19 = 8
-1p = 8

Divide each side by '-1'.
p = -8

Simplifying
p = -8

See similar equations:

| Y=-11y | | 3n+7n-2n=64 | | (4x-3)=(2x+7) | | 3m-2m+1=2 | | 75+1-32+16-1+32+16= | | 234-79= | | 3-2+5a-2a=12-1 | | 0=0.5h(B+3C) | | -6x-13=-3(4x+3) | | 4-5a=10a | | 5k+5+6k+2=84 | | 2x^2+56=x^2+15x | | 5-1/2x4 | | 10=5w-5 | | x*12-65x*6+64=0 | | -29=-8+3y | | 2x-3(9-2x)=-11 | | 5s-2=7+12 | | p-27=-48 | | 4x+1-x=19 | | 4x+3x+7= | | 4(5x+6)=4 | | 7^0/7^5 | | 10(2x+3)=100 | | 1/2(4x=6)=1/3(9x-24) | | (x-2)(x+3)(x-4)=0 | | 5.4/2g=9 | | 5.4/2x=9 | | 5x^2+11x=-3 | | sin(5*x)=0 | | 4/8x5/8 | | -1+4(p+5)=-37-3p |

Equations solver categories